Studies of bio waste materials from sago hampas and oil palm leaves for cell imaging applications - Shoriya Aruni, Abdul Manaf (2015)
Synthesizing of carbon nanospheres (CNSs) from bio waste is a good approach due to its availability, environmental friendly and low cost. On the other hand, utilization of bio waste to the high added value products attracts much attention where it can prevent the environmental problems due to its overload. Although there are many types of bio wastes available, very limited studies were attempted to use oil palm leaves (OPL) and sagohampas as the precursor for synthesizing carbon nanospheres. The CNSs were obtained by using a single step pyrolysis method in nitrogen atmosphere at different temperature in tube furnace without any catalysts support. For the OPL precursor, the pyrolysis temperaturesare 500 °C, 600 °C and 700 °C and for sago hampas, its temperatures are 400 °C and 600 °C, which has been identified using TGA analysis. The key approach is the natural silica bodies found in the precursor that plays important template role in the formation of CNSs. In addition, the lignocellulosic content in the bio waste also plays the role as a carbon source for the CNSs synthesis. Different pyrolysis temperature gives different effect on the pyrolyzed materials. The obtained CNSs were characterized by TGA, XRD, Raman, FTIR, FESEM-EDX, TEM and Zeta potential. The optimum temperature for the CNSs obtained from OPL is 600 °C. At this temperature, CNSs exhibit small sizes of particle,which is ~20 nm with uniform distribution of spherical shape particles under FESEM analysis. In addition, TEM with a high magnification view shows the particle size of 30 nm. The carbon content of CNSs at 600 °C gives highest value, which is 87.90 % compared to the other pyrolysis temperature. On the other hand, the CNSs obtained from sago hampasshow that the higher temperature gives better performance. The FESEM images show that the particle size is in the range of 60-70 nm whereas the TEM images exhibit the 50 nm of particle size with spherical shape observed. The carbon content at higher temperature gives 83.90 %, which is higher than the lower pyrolysis temperature. It shows that the different precursor gives different carbonizations effect depending on the pyrolysis temperature. The obtained CNSs were used for biotechnology applications which are cell imaging. The CNSswas tagged with fluorescent dye of Coumarin 6 (C-6). Few cell lines including UMR 106, A375, N2A and MDCK were used as biological model to observe CNSs ability as a nano carriers for drug delivery. The cellular uptake study observed under fluorescence microscope shows that the CNSs were efficiently taken up by the cell lines and cytotoxicity was determined by MTT assay method. From the results it shows that the CNSs can inhibit the cell proliferation of MDCK and N2A at low percentages whereas for A375 it can be clearly observed the apoptosis with dose dependent. This finding shows the alternative way to produce low cost and high value carbon nanospheres with spherical shape and porous structure by utilization of bio waste as a precursor. The CNSs can be applied in many other applications such as drug delivery, water purification and energy storage device.